2012
DOI: 10.1177/0009922812460333
|View full text |Cite
|
Sign up to set email alerts
|

Parent and Physician Perceptions of Medical Home Care for Children With Autism Spectrum Disorders in the State of Kentucky

Abstract: The medical home model of care is widely accepted as the ideal for children with autism spectrum disorders (ASDs) but may be very difficult to implement. In this study, parents of children with autism and pediatricians caring for children with autism in Kentucky were surveyed to determine the current status of primary care services for children with ASDs. Results indicated that the majority of families and physicians were comfortable with the routine health care provided to children with ASDs, but had concerns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Strunk et al () noted that some parents felt that providers treated them poorly and perceived them negatively as parents. Conversely, Williams et al () found that most parents of children receiving care in medical homes felt that HCPs provided a caring environment and were encouraging of parents' abilities.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Strunk et al () noted that some parents felt that providers treated them poorly and perceived them negatively as parents. Conversely, Williams et al () found that most parents of children receiving care in medical homes felt that HCPs provided a caring environment and were encouraging of parents' abilities.…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, they still experience unmet needs, despite their higher rate of utilization, greater expenditure, and longer time spent in medical appointments (Cheak‐Zamora & Farmer, ; Kogan et al, ; Kuhlthau et al, ; Strunk et al, ; Williams et al, ; Zuckerman et al, ). Although having a medical home is associated with fewer unmet needs (Cheak‐Zamora & Teti, ; Kogan et al, ) and greater satisfaction with care (Zuckerman et al, ), most children with ASD do not have medical homes (Williams et al, ). In fact, they are less likely to have a medical home than children in general and children with other special health care needs (Brachlow, Ness, McPheeters, & Gurney, ; Kogan et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the literature indicates that the core features of ASD in children can lead to behaviors that parents find challenging (Williams et al, 2012). These challenging behaviors can increase the level of anxiety and stress in parents of children with ASD in comparison to parents of children with other developmental disorders, and this may decrease parents' satisfaction with the effectiveness of intervention programs (Russell & McCloskey, 2016;Williams et al, 2012).…”
mentioning
confidence: 99%
“…In addition, the literature indicates that the core features of ASD in children can lead to behaviors that parents find challenging (Williams et al, 2012). These challenging behaviors can increase the level of anxiety and stress in parents of children with ASD in comparison to parents of children with other developmental disorders, and this may decrease parents' satisfaction with the effectiveness of intervention programs (Russell & McCloskey, 2016;Williams et al, 2012). This possibility is substantiated by research indicating that when parents are involved in the process of determining intervention goals for their children with ASD, the level of their anxiety and stress can decrease remarkably, and this can lead to increased satisfaction with the intervention programs used for their children (Bloch & Weinstein, 2009;Dunn, Cox, Foster, Mische-Lawson, & Tanquary, 2012;Guldberg et al, 2011).…”
mentioning
confidence: 99%
“…Research shows that various barriers have been identified in implementation [27,28]. Gaps have been uncovered between families' beliefs and the actual services received [29,30], including differences on care practices [31], professional insensitivity [32,33], and parental dissatisfaction with health care [34,35]. Parents' health concerns for CNDD also differ significantly from routinely addressed concerns during well-health visits [36].…”
Section: Introductionmentioning
confidence: 99%